PERLINDUNGAN HUKUM DAN PEMENUHAN HAK ANAK SESUAI PERMENDAGRI NOMOR 2 TAHUN 2016 TENTANG KARTU IDENTITAS ANAK DALAM RUANG LINGKUP PELAYANAN PUBLIK DI KABUPATEN LOMBOK TIMUR - Wijaya, Sandy Ari (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractLegal protection for every citizen is a mandatory thing that must be fulfilled in accordance with the mandate of the highest law of the Indonesian nation. One of the most basic things in fulfilling legal protection for citizens is a legality related to status and population data that will guarantee the rights of all citizens. The official residence identity as a form of legal protection for citizens aged 17 years is embodied in the Electronic Identity Card. In its development, official identity as an acknowledgment for citizens under 17 years of age began to be promoted with the Regulation of the Minister of Home Affairs Number 2 of 2016. Ages categorized as children by population were considered to have received the same treatment in terms of giving an identity card as a form of protection. and the realization of the fulfillment of the rights of children and adults. Legal protection and fulfillment of children's rights related to the Child Identity Card procurement program based on the Minister of Home Affairs Regulation Number 2 of 2016 in East Lombok Regency is a concrete step in an effort to realize aspects of public services for children, especially in accessing several government strategic programs with relevant stakeholders.Keywords: Child Identity Card; fulfillment of rights; legal protectionAbstrakPerlindungan hukum bagi setiap warga negara merupakan hal wajib yang harus dipenuhi sesuai amanat Undang-undang tertinggi bangsa Indonesia. Salah satu hal yang paling mendasar dalam pemenuhan perlindungan hukum bagi warga negara adalah sebuah legalitas terkait status dan data kependudukan yang akan menjamin hak-hak semua warga negara. Identitas kependudukan resmi sebagai wujud perlindungan hukum bagi warga Negara yang berusia 17 tahun terwujud dalam Kartu Tandap Penduduk Elektronik. Dalam perkembangannya identitas resmi sebagai pengakuan untuk warga Negara yang berusia di bawah 17 tahun mulai digalakkan dengan Peraturan Menteri Dalam Negeri Nomor 2 Tahun 2016. Usia yang dikategorikan sebagai anak-anak secara kependudukan dinilai harus mendapatkan perlakuan yang sama dalam hal pemberian kartu identitas sebagai wujud perlindungan dan perwujudan pemenuhan hak anak dan orang dewasa. Perlindungan hukum dan pemenuhan hak anak terkait program pengadaan Kartu Identitas Anak berdasarkan Peraturan Menteri Dalam Negeri Nomor 2 Tahun 2016di Kabupaten Lombok Timur merupakan sebuah langkah konkret dalam upaya mewujudkan aspek pelayanan publik bagi anak terutama dalam mengakses beberapa program strategi pemerintah dengan stakeholder terkait.